2020
DOI: 10.1093/cercor/bhz301
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Similarity Analyses of FrontoParietal Task Coding: Individual Variation and Genetic Influences

Abstract: Pattern similarity analyses are increasingly used to characterize coding properties of brain regions, but relatively few have focused on cognitive control processes in FrontoParietal regions. Here, we use the Human Connectome Project (HCP) N-back task functional magnetic resonance imaging (fMRI) dataset to examine individual differences and genetic influences on the coding of working memory load (0-back, 2-back) and perceptual category (Face, Place). Participants were grouped into 105 monozygotic twin, 78 dizy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
(104 reference statements)
3
12
0
Order By: Relevance
“…Current theoretical and empirical work has suggested a domain-general cognitive control capacity ( Assem et al, 2020 ; Kan et al, 2013 ; Miyake and Friedman, 2012 ), which enables flexible adaptation of thoughts and actions to fulfill a variety of task goals and demands ( Cole et al, 2013 ; Braver, 2012 ). Yet this hypothesis could not be tested in prior studies using twin-based neuroimaging designs, since they relied on evaluating heritability of neural activation in single cognitive control tasks ( Etzel et al, 2020 ; Koten et al, 2009 ; Matthews et al, 2007 ). Our work significantly extends these prior findings by demonstrating that twin similarity effects generalize across multiple cognitive control tasks; tasks which tap into different processes within this domain (e.g., selective attention, task-switching, working memory).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current theoretical and empirical work has suggested a domain-general cognitive control capacity ( Assem et al, 2020 ; Kan et al, 2013 ; Miyake and Friedman, 2012 ), which enables flexible adaptation of thoughts and actions to fulfill a variety of task goals and demands ( Cole et al, 2013 ; Braver, 2012 ). Yet this hypothesis could not be tested in prior studies using twin-based neuroimaging designs, since they relied on evaluating heritability of neural activation in single cognitive control tasks ( Etzel et al, 2020 ; Koten et al, 2009 ; Matthews et al, 2007 ). Our work significantly extends these prior findings by demonstrating that twin similarity effects generalize across multiple cognitive control tasks; tasks which tap into different processes within this domain (e.g., selective attention, task-switching, working memory).…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in higher cognitive processes and general fluid intelligence have been closely linked to variation in the neural activations and functional connectivity within the fronto-parietal regions ( Cole et al, 2012 ; Duncan et al, 2020 ). In our own prior work ( Etzel et al, 2020 ), we identified clear patterns of fronto-parietal genetic variation related to cognitive control, using a twin-based design and multivariate pattern similarity approach with the N-back task. Nevertheless, the current study departs from our prior one and from other neuroimaging work, in that those prior studies were able to directly estimate genetic heritability effects by incorporating dizygotic (fraternal) as well as monozygotic twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, our paradigm did not tap into the contribution of individual perceptional differences to the current results. As a matter of fact, interindividual variability in perception may be genetically determined ( Etzel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing whole dissimilarities among all task conditions in RDM, RSA becomes an effective approach to track the multidimensional representation among task conditions. On the one hand, researchers can construct hypothesis-based RDM for different conditions, then compare these theoretical models with RDMs from real neural activities to calculate how similar they are (Alfred et al, 2018 ; Feng et al, 2018 ; Hall-McMaster et al, 2019 ; Yokoi and Diedrichsen, 2019 ; Etzel et al, 2020 ). As a result, they can infer the information is coded in the brain.…”
Section: Representational Similarity Analysis Using Neuroramentioning
confidence: 99%